System of Business Cycle Efficiency Indicators on the Value Added Basis: Analysis in the Context of the Capital Transformation Stages - DMITRI A. Pankov; Ju. . Kuhto Julia (Учёт. Анализ. Аудит)
The scientific research relevance is conditioned by the necessity of the in-depth analysis of business-cycle results at each stage of the capital turnover in order to find effective ways out of recession and provide gradual and systematic stimulus to economic growth from a particular organization to the national economy as a whole. Research methods: general scientific method of knowledge, analysis, synthesis, induction, deduction, scientific abstraction, simulation, comparing, reasoning by analogy, a systematic approach. In our research the authors consider a new object of accounting (value added) in the context of the stages of capital turnover. The proposed accounting and analysis method based on the value added makes it possible to track its formation and movement along the entire chain of capital transformation and in relation to its monetary backing. Results and their novelty: we have developed the system of business process efficiency indicators based on value added in conjugation with stages of capital transformation, in the context of real monetary backing from the perspective of a differentiated approach to “filling” economic turnover indicators for the management’s purposes at the micro and macro level, which significantly expands the information base of financial management and enables us to establish convergence in the financial flows management at various economic managements levels.